Fiscal Stimulus in a Credit Crunch: The Role of Wage Rigidity - Francesco Furlanetto (Norges Bank, 2009)
In this paper we study the impact of an expansion in public spending in a credit constrained economy with sticky wages. The flexible wage version of the model implies strong expansionary effects on output and consumption but also a counterfactual increase in real wages. The introduction of sticky wages, besides being a realistic addition, solves these problems and preserves the expansionary effects on output and consumption. Moreover, once we introduce segmentation in the labor market, sticky wages are even essential to obtain expansionary effects.
hdl:11250/2497636
Keywords: E32; E62; 330; sticky wages; rule-of-thumb consumers; fiscal shocks; financial frictions